How do firms cope with losses from extreme weather events? - Emanuela Benincasa; Frank Betz; Luca Gattini (European Investment Bank (EIB), 2022)
We document the investment and financing decisions of firms that experience monetary losses due to extreme weather events. Our sample covers firms operating in 41 economies, mainly emerging and developing markets. Consistent with the need to either replenish damaged capital or to adapt to climate change, firms hit by extreme weather are more likely to invest in long-term assets. In addition, they are more likely to integrate climate-friendly measures in their production processes. Although these firms have higher needs for bank credit, they are not more likely to be credit constrained than the average firm. Nonetheless, they face higher loan rejection rates and they are more leveraged than otherwise comparable firms. This suggests that climate change has the potential to erode the quality of firm balance sheets over time.
Keywords: D22; G21; G32; L20; Q54; 330; Physical climate risk; Extreme weather; Access to credit; Corporate investment